Reactive hydrocarbons in the atmosphere (Academic Press, 1999)
The book provides comprehensive and up-to-date reviews covering all aspects of the behavior, sources, occurence, and chemistry of the organic compounds. Both biogenic and anthropogenic sources are considered, as are their effects in the atmosphere at local, regional, and global scales